2017
DOI: 10.18632/oncotarget.19958
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative and pro-apoptotic effects induced by simultaneous inactivation of HER1 and HER2 through endogenous polyclonal antibodies

Abstract: The human epidermal growth factor receptor (HER1) and its partner HER2 are extensively described oncogenes and validated targets for cancer therapy. However, the effectiveness of monospecific therapies targeting these receptors is hampered by resistance emergence, which is frequently associated with the upregulation of other members of HER family. Combined therapies using monoclonal antibodies or tyrosine kinase inhibitors have been suggested as a promising strategy to circumvent this resistance mechanism. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Poly Abs can simultaneously target multiple epitopes of the same or different TAAs. Study indicated that simultaneous inactivation of HER1 and HER2 by specific Poly Abs was able to reduce the viability of a panel of human tumor lines with differential expression levels of HER1 and HER2, and circumvent the resistance mechanism 25 . There is growing recognition that the treatment effect of tumor immunotherapy is affected by many factors besides the antigenicity and/or mutational burden of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Poly Abs can simultaneously target multiple epitopes of the same or different TAAs. Study indicated that simultaneous inactivation of HER1 and HER2 by specific Poly Abs was able to reduce the viability of a panel of human tumor lines with differential expression levels of HER1 and HER2, and circumvent the resistance mechanism 25 . There is growing recognition that the treatment effect of tumor immunotherapy is affected by many factors besides the antigenicity and/or mutational burden of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal antibodies can target several epitopes of the same or different tumor-associated antigens. According to the findings, targeting human epidermal growth factor receptor (HER) 1 and HER2 by particular polyclonal antibodies reduced the viability of a panel of human tumor lines with different HER1 and HER2 expression levels, overcoming the tumor resistance mechanism( 21 ). However, non-specific interaction with the non-tumor antigens or non-target antigens can limit polyclonal antibody applications.…”
Section: Discussionmentioning
confidence: 99%
“…The effects were associated to direct inhibition of EGF-R activation rather than to receptor internalization and degradation, as the total receptor levels (assessed with a control anti-EGF-R that does not depend on target phosphorylation status for recognition) did not vary upon antibody treatments. Future studies of receptor internalization induced by the antibodies could be performed using a suitable experimental setting, with longer treatment of the cells (8 h or more) as previously described 26 .…”
Section: Affinity Increases Translated Into Enhanced Inhibitory Capacmentioning
confidence: 99%